Science and the garden : the scientific basis of horticultural practice - Ingram, David S.; Vince-Prue, Daphne; Gregory, P. J. (Chichester, West Sussex : John Wiley & Sons, Inc., 2016)
Most conventional gardening books concentrate on how and when to carry out horticultural tasks such as pruning, seed sowing and taking cuttings. Science and the Garden, Third Edition is unique in explaining in straightforward terms some of the science that underlies these practices. It is principally a book of 'Why' ' Why are plants green' Why do some plants only flower in the autumn' Why do lateral buds begin to grow when the terminal bud is removed by pruning' Why are some plants successful as weeds' Why dus climate variability and change mean change for gardeners' But it also gus on to deal with the 'How', providing rationale behind the practical advice. The coverage is wide-ranging and comprehensive and includes: the diversity, structure, functioning and reproduction of garden plants; nomenclature and classification; genetics and plant breeding; soil properties and soil management; environmental factors affecting growth and development; methods of propagation; size and form; colour, scent and sound; climate; environmental change; protected cultivation; pest, disease and weed diversity and control; post-harvest management and storage; garden ecology and conservation; sustainable horticulture; gardens and human health and wellbeing; and gardens for science. This expanded and fully updated Third Edition of Science and the Garden includes two completely new chapters on important topics: -Climate and Other Environmental Changes -Health, Wellbeing and Socio-cultural Benefits Many of the other chapters have been completely re-written or extensively revised and expanded, often with new authors and/or illustrators, and the remainder have all been carefully updated and re-edited. Published in collaboration with the Royal Horticultural Society, reproduced in full colour throughout, carefully edited and beautifully produced, this new edition remains a key text for students of horticulture and will also appeal to amateur and professional gardeners wishing to know more about the fascinating science behind the plants and practices that are the everyday currency of gardening.
Diversity in the plant world -- The plant body : structure and function -- Reproduction : securing the future -- Naming plants -- Selecting and breeding plants -- Soils and roots -- Soil cultivation and fertility -- The plant environment : light and water -- Plants and seasons -- Growing plants from seed -- Vegetative propagation -- Size and form -- Colour, scent, and sound in the garden -- Climate and weather -- Climate and other environmental changes -- Protected cultivation -- The diversity of the undesirables -- Controlling the undesirables -- Maturation, ripening, and storage -- Garden ecology -- Garden wildlife and conservation -- Low input and low impact gardening -- Health, well being and socio-cultural benefits -- Gardens for science.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Horticulture; Gardening; GARDENING -- Essays; GARDENING -- Reference; GARDENING -- Vegetables; SCIENCE -- Life Sciences -- Horticulture; Gardening; Horticulture; Electronic books; Electronic books